In vitro activation of human T and B lymphocytes by pokeweed mitogen. - Mellstedt, H (1975)
In previous in vitro studies the DNA synthesis in human blood lymphocytes induced by low concentration of PWM correlated with the percentage of bone marrow-derived (B) lymphocytes in cell suspensions. No correlation with lymphocyte subpopulations was noted when lymphocytes were activated by high concentrations of PWM. In this paper the hypothesis that low concentration of PWM mainly activates B lymphocytes was tested by measuring the [14C]thymidine incorporation into purified T or B lymphocytes from healthy donors. B lymphocytes were purified to 90--95% by buoyant density centrifugation of T lymphocytes rosetted with sheep red blood cells. T lymphocytes were enriched by passage of lymphocytes through an IgG-anti-IgG-coated column. Low concentration of PWM-stimulated B lymphocytes but not T lymphocytes, while high concentrations of the stimulant activated both cell types. It was also noted that the B- but not the T-lymphocyte fraction contained cells which synthesized DNA in the absence of PWM.